2020
DOI: 10.3390/nano10061045
|View full text |Cite
|
Sign up to set email alerts
|

Novel Exfoliation of High-Quality 2H-MoS2 Nanoflakes for Solution-Processed Photodetector

Abstract: Highly dispersive molybdenum disulfide nanoflakes (MoS2 NFs), without any phase transition during the exfoliation process, are desirable for full utilization of their semiconductor properties in practical applications. Here, we demonstrate an innovate approach for fabricating MoS2 NFs by using hydrazine-assisted ball milling via the synergetic effect of chemical intercalation and mechanical exfoliation. The NFs obtained have a lateral size of 600–800 nm, a thickness less than 3 nm, and high crystallinity in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 38 publications
0
40
0
Order By: Relevance
“…Mechanical exfoliation, also known as micromechanical cleavage, is a straightforward technique that takes advantage of the weak bonding between layers, for the production of high-quality mono-to few-layer MoS 2 [58][59][60]. It consists of exfoliating thin films of 2D-MoS 2 from a bulk MoS 2 crystal by using a low surface tension tape to break the weak interlayer bonds in a similar way as for grapheme [61].…”
Section: Mechanical and Chemical Exfoliationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical exfoliation, also known as micromechanical cleavage, is a straightforward technique that takes advantage of the weak bonding between layers, for the production of high-quality mono-to few-layer MoS 2 [58][59][60]. It consists of exfoliating thin films of 2D-MoS 2 from a bulk MoS 2 crystal by using a low surface tension tape to break the weak interlayer bonds in a similar way as for grapheme [61].…”
Section: Mechanical and Chemical Exfoliationsmentioning
confidence: 99%
“…Chemical exfoliation, on the other hand, appears as a promising approach to produce large quantities of mono-and few-layer MoS 2 nanosheets [60,[63][64][65]. Eda et al [54] reported a high yield of monolayer crystal synthesis using chemical exfoliation of bulk MoS 2 via Li intercalation.…”
Section: Mechanical and Chemical Exfoliationsmentioning
confidence: 99%
“…51 Additionally, ball milling has the ease of coupling with numerous auxiliary methods to obtain nanostructure-like sheets and akes of the desired dimensions and composition by altering the process conditions. 2,26,50,52,53 Therefore, we proposed ultrasonic-assisted ball milling. The preparation method reduces the size of MoS 2 by ball milling on the one hand, and obtains few-layer MoS 2 by ultrasonic peeling on the other hand.…”
Section: Introductionmentioning
confidence: 99%
“…MoS 2 , a family of TMDCs, has been used as a building block for 2D field-effect transistors due to its high carrier mobility and excellent on-off ratios [ 8 , 9 , 10 ]. In addition, due to its exceptional physicochemical properties, 2D MoS 2 has been extensively used for novel 2D electronics, flexible optoelectronics, and efficient catalysis [ 11 , 12 , 13 , 14 , 15 ]. When MoS 2 is thinned down to a monolayer, its electronic structure and physical symmetries are radically altered, resulting in new physical behavior such as indirect to direct bandgap transitions [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%